DO CAPITAL ADEQUACY AND INTEREST MARGIN DETERMINE BANK PROFITABILITY? EMPIRICAL EVIDENCE FROM INDONESIA - Akhmad Ghozali (TECHNOBIZ : International Journal of Business, 2026)
Bank profitability is a crucial indicator of the stability and sustainability of the financial sector. Although previous studies have highlighted the role of capital adequacy and interest margin, empirical evidence in Indonesia remains limited and inconsistent, particularly during the post-pandemic economic recovery period. This study examines the effects of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and economic growth (Gross Domestic Product, GDP) on Return on Equity (ROE) of publicly listed banks in Indonesia from 2019 to 2024. Panel regression results show that NIM has a positive and significant effect on ROE, confirming that effective interest income management is a key factor in enhancing bank profitability. In contrast, CAR and GDP are not significant, indicating that capital levels and economic growth do not directly contribute to profitability during the observed period. The study emphasizes the importance of evaluating the effectiveness of capital policies and the influence of macroeconomic factors on bank performance. The findings provide empirical contributions to the banking literature and offer strategic guidance for regulators and bank management in designing policies and strategies to improve profitability in an adaptive and sustainable manner.